The Role of Exopolysaccharides in Direct Interspecies Electron Transfer - Zhuang, Zheng; Xia, Xue; Yang, Guiqin; Zhuang, Li (Frontiers in Microbiology, 2022)
Direct interspecies electron transfer (DIET) is an effective mechanism for microbial species to exchange electrons cooperatively during syntrophic metabolism. It is generally accepted that DIET is mainly mediated by electrically conductive pili and outer surface c-type cytochromes (c-Cyts). However, as an extracellular matrix ubiquitous and abundant on the surface of microorganisms, the effect and mechanism of exopolysaccharides on DIET is still unclear. This study constructed a co-culture of exopolysaccharides-deficient Geobacter sulfurreducens with Geobacter metallireducens to explore the role of exopolysaccharides in DIET. Results revealed that the deficiency of exopolysaccharides extended the metabolic period of the co-culture by 44.4%, and changed the proportions of each species in the co-culture. The exopolysaccharides-deficient co-culture failed to form large, tight spherical aggregates, and the expression of c-Cyts and pili was decreased. The addition of magnetite and GAC respectively might compensate for the functions of c-Cyts and pili in the first generation of co-culture, but the stimulatory effect on the metabolic stable period co-culture was fairly limited. These findings demonstrate that non-conductive exopolysaccharides are an important component of DIET aggregates and an extracellular matrix for DIET-required c-Cyts.